The supramolecular chemistry of lipid oxidation and antioxidation in bulk oils - Budilarto, Elizabeth S (Eur J Lipid Sci Technol, 2015)
The microenvironment formed by surface active compounds is being recognized as the active site of lipid oxidation. Trace amounts of water occupy the core of micro micelles and several amphiphilic minor components (e.g., phospholipids, monoacylglycerols, free fatty acids, etc.) act as surfactants and affect lipid oxidation in a complex fashion dependent on the structure and stability of the microemulsions in a continuous lipid phase such as bulk oil. The structures of the triacylglycerols and other lipid-soluble molecules affect their organization and play important roles during the course of the oxidation reactions. Antioxidant head groups, variably located near the water-oil colloidal interfaces, trap and scavenge radicals according to their location and concentration. According to this scenario, antioxidants inhibit lipid oxidation not only by scavenging radicals via hydrogen donation but also by physically stabilizing the micelles at the microenvironments of the reaction sites. There is a cut-off effect (optimum value) governing the inhibitory effects of antioxidants depending inter alias on their hydrophilic/lipophilic balance and their concentrations. These complex effects, previously considered as paradoxes in antioxidants research, are now better explained by the supramolecular chemistry of lipid oxidation and antioxidants, which is discussed in this review.